Predicting return on equity based on significant determinants for Islamic banks in Malaysia / Nur Liyana Basir and Rashidah Ismail - Basir, Nur Liyana; Ismail, Rashidah (2017)
The existence of Islamic banks that grow rapidly in every corner of the world has caused strong competition among them and other conventional banks in Malaysia. This requires the banks management to choose wisely on the determinants that make them to remain strong and relevant in the Islamic banking sector. The main purpose of this study is to predict the return on equity of some Islamic banks in Malaysia using forecast value of significant banking determinant. The significant banking determinants selected for the study include deposit ratio, operating efficiency and market concentration. The study utilized secondary data from year 2010 until year 2016 for 13 Islamic banks in Malaysia. Principal Component Analysis was applied in order to get internal and external significant determinants. The internal and external significant determinants are Bank Size and Gross Domestic Product. Then, Multiple Linear Regression was used to formulate the Bank Profit Model which shows the relationship between the Bank Size and GDP with Return on Equity. Next, Geometric Brownian Motion used to forecast the value of Bank Size and GDP. The forecast value was substitute into Bank Profit Model to calculate the Return on Equity for each bank. From the results of the study, management of bank can have focused on Bank Size and Gross Domestic Product in order to gain more profit. Besides, the Return on Equity for Islamic banks in this study in a range of 3 percent to 23.82 percent.